Severe Immune-Related Cutaneous Vasculitis Induced by Osimertinib - Calderon, Benoit; Vazquez, Léa (Archives of Clinical and Medical Case Reports, 2022)
Osimertinib is a third-generation epidermal growth factor receptor (EGFR)- tyrosine kinase inhibitors (TKIs) which is the current standard of care for first-line treatment of advanced EGFR+ Non-Small Cell Lung Cancer (NSCLC). The most common Osimertinib-related adverse events (AEs) are hematologic toxicity, rash, dry skin, and paronychia which are usually tolerable and manageable. Serious AEs occur infrequently and the etiopathogenesis of some remains unclear. We present a case of grade 3 cutaneous vasculitis induced by osimertinib in a Caucasian woman that required immunosuppressive therapy.